Producing organic vegetables for better health - Singh, S. K.; Yadava, R. B.; Chaurasia, S.N. S.; Prasad, R. N.; Singh, Raghwendra; Chaukhande, Paresh; Singh, B. (Indian Horticulture, 2019)
In recent years, major emphasis is given for commercial exploitation of vegetable crops as they are nutritionally rich, high-yielding and provide a valuable source of income. The study revealed that organic production of vegetable is economically-feasible and viable, besides it also improves quality, taste and flavour through increased dry-matter content, vitamin C, phenolic compounds and protein content. The soil heath is improved through increased organic carbon content, microbial activity and availability of nutrients and water.